Pengaruh Kemitraan dan Kewirausahaan Terhadap Saluran Distribusi, serta Pengaruhnya Terhadap Kinerja UMKM di Kabupaten Purbalingga - Sugeng Rianto; Kurniawan Kurniawan (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
Sub-sector of farms broiler chickens in the District of Purbalingga is a business strategy the interrelationship between farmers and livestock feed company. One of the strategies of feed cattle for profit is to develop a distribution system so as to develop partnerships broiler farms. Research on strategy choice partnership is one form of strategic alliances that can improve business performance through some influence that is a partnership (relationship), entrepreneurship and distribution (distribution channel).